Yogyakarta Tourism Office's Strategy in Economic Recovery of the Tourism Sector During the Covid-19 Pandemic - Shelly Christiani Saputri; Putri Hergianasari; Wilson M.A. Therik (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2022)
This study aims to explain the strategy of the Yogyakarta Tourism Office in the economic recovery of the tourism sector during the Covid-19 period. So far, tourism has become the fourth largest sector that contributes to the country's foreign exchange after palm oil (CPO), oil and gas and mining (coal). The world of tourism has been hit by the Covid-19 pandemic. Since the Covid-19 outbreak, all sectors have experienced a drastic decline, including the tourism sector, which has been in the second position as Indonesia's second largest foreign exchange contributor. This pandemic condition is forcing tourists to cancel their travel plans to Indonesia, one of which is the city of Yogyakarta. Based on statistics, Yogyakarta has the title of the tourism city most affected by the Covid-19 pandemic. In just over a year, the tourism industry in the city of Yogyakarta suffered losses of up to Rp. 10 trillion. This is because Yogyakarta is the second most popular tourist destination in Indonesia after Bali. It is undeniable that Yogyakarta tourism has a great influence on the community's economy. The method used in this study is a qualitative method with a descriptive type of research. The findings of this study are the Yogyakarta’s Government Tourism Office (Dinpar) in its efforts to restore the tourism sector economy through the implementation of the Covid-19 protocol; new normal policy; implementation of CHSE (Cleanliness, Health, Safety, and Environment Sustainability); restoration of MICE (meetings, incentives, conventions, exhibitions); domestic tourism; and events gradually; revitalization of the agrarian sector through the development of agribusiness.